Fundamentals of Estuarine Physical Oceanography - Bruner de Miranda, Luiz; Andutta, Fernando Pinheiro; Kjerfve, Björn; Castro Filho, Belmiro Mendes de (Ocean Engineering & Oceanography, 2017)
This book provides an introduction to the complex system functions, variability and human interference in ecosystem between the continent and the ocean. It focuses on circulation, transport and mixing of estuarine and coastal water masses, which is ultimately related to an understanding of the hydrographic and hydrodynamic characteristics (salinity, temperature, density and circulation), mixing processes (advection and diffusion), transport timescales such as the residence time and the exposure time. In the area of physical oceanography, experiments using these water bodies as a natural laboratory and interpreting their circulation and mixing processes using theoretical and semi-theoretical knowledge are of fundamental importance. Small-scale physical models may also be used together with analytical and numerical models. The book highlights the fact that research and theory are interactive, and the results provide the fundamentals for the development of the estuarine research.